PENERAPAN DISCOVERY LEARNING UNTUK MENANAMKAN KARAKTER KEWIRAUSAHAAN MAHASISWA PADA MATA KULIAH MANAJEMEN RITEL - Maisaroh Maisaroh (Universitas Sebelas Maret, 2019)
This research tried to develop the learning method through class action using discovery learning methods, on Retail Management classes. Before learning process is carried out, the lecturer developed learning methods, began with designing instructional learning, consisted of the objectives of learning, assessment, and implementation of learning. The learning process was held during 16 meetings, divided into 4 learning outcomes. The discovery learning in this research then elaborated used three learning techniques, those are an industrial internship, case study, and group discussions. Based on the results, all learning outcomes are achieved, with value for every learning outcome ≥ 79%. The level of activeness and the presence of students are ≥ 79.5%. It shows that the discovery learning method gives a positive impact in building the entrepreneurship character, both from aspect cognitive abilities (in the form of mastery of material) and aspect affective abilities (creativity, activeness, presence, the courage to express opinions). Besides that the productivity and performance of lecturers also achieved. Those can be seen from the availability of learning tools, and performance measurement from 3.2 in the previous semester to 3.7 in the relevant semester. It means the discovery learning method has a positive impact on the learning process, both for students and lecturer.Keywords: Retail Management, Entrepreneurship, Entrepreneur character, Discovery Learning